RENDEMEN AND CHARACTERISTICS OF PEKTINS RED DRAGON FRUIT LEATHER (Hylocereus costaricensis) WITH THE DIFFERENCE IN EXTRACTION METHOD AND TIME - Devi Silsia; Magrisa Febreini; Laili Susanti (BPFP Faperta UNIB, 2021)
This study aims to determine the effect of the method and time of extraction on the yield and characteristics of pektin red dragon fruit leather according to the SNI pektin (01-2238-1991) and the International Pektin Producers Association (IPPA) 2003. The experimentals design was a Completely Randomized Design with 2 factors. The first factor was the extraction method used, namely (M1 = conventional method, M2 = ultrasonik method). The second factor was extraction time (W1 = 15 minutes, W2 = 30 minutes, W3 = 60 minutes, and W4 = 90 minutes. The results showed that the extraction method had a significant effect on yield, equivalent weight, galacturonic acid content, degree of esterification, water content and ash content, but had no significant effect on methoxyl content. Extraction time significantly affected yield, equivalent weight, methoxyl content, galacturonic acid content, degree of esterification, water content and ash content. While the interaction of the two treatments had a significant effect on yield, equivalent weight, and water content. The highest yield was obtained using the ultrasonik method for 60 minutes with a value of 13.57%. The equivalent weight that meets IPPA (2003) and SNI pektin standards (01-2238-1991) is found in conventional and ultrasonik methods at 30 and 60 minutes.